2012
DOI: 10.1007/s11746-012-2094-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Added Conjugated Linoleic Acid and Iodine Concentrations on Conjugated Linoleic Acid‐Rich Soy Oil Oxidative Stability

Abstract: Jain and Proctor [1] reported pilot scale production of 20 % conjugated linoleic acid (CLA) in soy oil by photoisomerization of soy oil linoleic acid (LA) in oil triacylglycerides to CLA using an iodine catalyst. Recently, we reported in a food oil oxidation study of freshly produced CLARSO that the pro-oxidant effect of CLA and iodine was independent of concentration [2]. However, the study did not distinguish between the effect of CLA and iodine on CLA oxidation. Removal of iodine may be important if iodine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A rutheniumon-carbon catalyst is combined with the oil in a high temperature, vacuum distillation technique as used in the deodorization step in general oil processing. The catalyst can be centrifuged and filtered out of the oil in a relatively simple process, rendering the oil safe for human consumption [12].…”
Section: Introductionmentioning
confidence: 99%
“…A rutheniumon-carbon catalyst is combined with the oil in a high temperature, vacuum distillation technique as used in the deodorization step in general oil processing. The catalyst can be centrifuged and filtered out of the oil in a relatively simple process, rendering the oil safe for human consumption [12].…”
Section: Introductionmentioning
confidence: 99%
“…1 3 in industry. Unlike the iodine-catalyzed photoisomerization process [11], the ruthenium catalyst can easily be centrifuged and filtered out of the oil [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, there were no effects of CLA levels on the amounts of volatiles, suggesting that in CLARSO residual iodine had a much greater effect than CLA levels on oxidation. Therefore, Yettella et al [11], then studied the effects of CLA levels and Iodine concentration on CLARSO oxidative stability and demonstrated that iodine diminished the CLA concentration effect, i.e. the rate of oxidation was constant in the presence of iodine and independent of CLA concentration.…”
Section: Introductionmentioning
confidence: 99%